2021
DOI: 10.1177/0310057x20962113
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of routine diagnostic test reduction interventions in patients admitted to the intensive care unit: A systematic review and meta-analysis

Abstract: Reducing unnecessary routine diagnostic testing has been identified as a strategy to curb wasteful healthcare. However, the safety and efficacy of targeted diagnostic testing strategies are uncertain. The aim of this study was to systematically review interventions designed to reduce pathology and chest radiograph testing in patients admitted to the intensive care unit (ICU). A predetermined protocol and search strategy included OVID MEDLINE, OVID EMBASE and the Cochrane Central Register of Controlled Trials f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Although there are a substantial number of studies reporting interventions to reduce unnecessary diagnostic testing in ICU, the quality of these studies is generally low, and none report a theorybased framework for intervention development. 3 Consequently, the safety and efficacy of targeted testing interventions remains uncertain. In contrast to existing studies, TICTOC has sought to identify and extract previously reported BCTs and use these to create a comprehensive targeted test reduction intervention with the aim of conducting a pivotal RCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there are a substantial number of studies reporting interventions to reduce unnecessary diagnostic testing in ICU, the quality of these studies is generally low, and none report a theorybased framework for intervention development. 3 Consequently, the safety and efficacy of targeted testing interventions remains uncertain. In contrast to existing studies, TICTOC has sought to identify and extract previously reported BCTs and use these to create a comprehensive targeted test reduction intervention with the aim of conducting a pivotal RCT.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review investigating the association between ICU targeted testing and hospital mortality was recently conducted, and the methods and findings were reported. 3 This review was used to develop the components of the TICTOC intervention by identifying, extracting, and classifying all BCTs reported in eligible studies. 6 This created a long list of possible components for the candidate intervention that was reviewed by the TICTOC management committee to identify any gaps.…”
Section: Identifying Successful Targeted Testing Behavioural Change Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…5 As many as half of all tests may not be clinically indicated, 6,7 and some are harmful due to their contribution to the development of anaemia. 8 In addition, considerable time is spent performing, processing and interpreting tests.…”
mentioning
confidence: 99%